Staphylococcus aureus β-Toxin Exerts Anti-angiogenic Effects by Inhibiting Re-endothelialization and Neovessel Formation - Tran, Phuong M.; Tang, Sharon S.; Salgado-Pabón, Wilmara (Frontiers in Microbiology, 2022)
Staphylococcus aureus causes severe, life-threatening infections that often are complicated by severe local and systemic pathologies with non-healing lesions. A classic example is S. aureus infective endocarditis (IE), where the secreted hemolysin β-toxin potentiates the disease via its sphingomyelinase and biofilm ligase activities. Although these activities dysregulate human aortic endothelial cell activation, β-toxin effect on endothelial cell function in wound healing has not been addressed. With the use of the ex vivo rabbit aortic ring model, we provide evidence that β-toxin prevents branching microvessel formation, highlighting its ability to interfere with tissue re-vascularization and vascular repair. We show that β-toxin specifically targets both human aortic endothelial cell proliferation and cell migration, while having a limited effect on endothelial cell rearrangement into capillary-like networks in vitro. Proteome arrays specific for angiogenesis-related molecules provided evidence that β-toxin promotes an inhibitory profile in endothelial cell monolayers, specifically targeting production of TIMP-1, TIMP-4, and IGFBP-3 to counter the effect of a pro-angiogenic environment. Dysregulation in the production of these molecules is known to result in sprouting defects (including deficient cell proliferation, migration, and survival), vessel instability and/or vascular regression. When endothelial cells are grown under re-endothelialization/wound healing conditions, β-toxin decreases the pro-angiogenic molecule MMP-8 and increases the anti-angiogenic molecule endostatin. Altogether, the data indicate that β-toxin is an anti-angiogenic virulence factor and highlight a mechanism where β-toxin exacerbates S. aureus invasive infections by interfering with tissue re-vascularization and vascular repair.